Comparisons of psychological distress and self-stigma among three types of substance use disorders receiving treatment-as-usual approaches: real-world data from a 9-month longitudinal study - Kun-Chia Chang; Hsin-Pao Chen; Shih-Wei Huang; Jung-Sheng Chen; Marc N. Potenza; Amir H. Pakpour; Chung-Ying Lin (SAGE Publishing, 2022)
Background: Substance use is an important issue worldwide and people with substance use disorders (SUDs) have been reported to have high levels of psychological distress and self-stigma. Therefore, psychological distress and self-stigma in people with SUDs are considerable. Objective: The present study used a longitudinal design to examine whether treatment-as-usual approaches in Taiwan improve psychological distress and self-stigma among people with three types of SUDs (heroin, amphetamine, and alcohol use disorders). Design: A 9-month longitudinal design involving four assessments spaced 3 months apart. Methods: Convenience sampling was used to recruit people with heroin ( n  = 112), amphetamine ( n  = 151), and alcohol ( n  = 56) use disorders from outpatient psychiatric center in Southern Taiwan. Psychological distress was assessed using the Depression, Anxiety, Stress Scale (DASS-21), and self-stigma was assessed using the Self-Stigma Scale-Short (SSS-S). Generalized estimating equation (GEE) models were constructed to understand between-group differences in psychological distress and self-stigma over time. Results: Patients with heroin and amphetamine use disorders had lower levels of psychological distress as compared with those with alcohol use disorder. Levels of psychological distress were lower at Time 2 to Time 4 as compared with Time 1. Patients with heroin and amphetamine use disorders had higher levels of self-stigma as compared with those with alcohol use disorder. Self-stigma levels remained stable over time. The dropout rate of receiving treatment-as-usual approach in the 9-month study was 60%. Conclusion: Treatment as usual for SUDs among outpatients in Taiwan may decrease psychological distress but not self-stigma. However, such effects need to be further examined given the high drop-out rates and absence of a control condition. The findings suggest that self-stigma may warrant additional treatment for patients with SUDs.